Psychosocial effects of SNS use: A longitudinal study focused on the moderation effect of social capital - Yoo, Ji Hye; Jeong, Eui Jun (Computers in human behavior, 2017)
As represented by “Facebook depression” and “alone together,” the effects of SNS use on a person's psychosocial well-being have been highlighted of late, but it is still unclear if SNS use adversely affects the users in psychosocial terms. In addition, there have been few studies that verified the moderating role of social capital in the relationship between SNS use and psychosocial factors. Using the one-year longitudinal panel data of 477 subjects, the current study tested the effects of SNS use and network size on psychosocial well-being factors (i.e., depression, loneliness, and life satisfaction). To clarify the accumulative effects of the variables on one another, the concept of “reciprocal influences” was also applied in the analysis. The results show different results of SNS use according to the degree of social capital. For the lower-social-capital group, a “vicious circle” was observed: depression augmented SNS use, but the increase of SNS use reinforced the degree of depression. Conversely, for the higher-social-capital group, a “virtuous circle” was found: SNS use increased the network size, and the increased network size strengthened the degree of life satisfaction. These results imply that social capital is a key factor in explaining and predicting the effects of SNS use. The theoretical contributions and practical implications of the study based on the empirical findings are discussed herein. •Effects of SNS use and social capital on psychosocial factors were tested.•Social capital was a key in explaining and predicting the effects of SNS use.•For the lower-social-capital group, a “vicious circle” was observed.•Depression augmented SNS use, but the increased SNS time reinforced depression.•For the higher group, network size enforced by SNS increased life satisfaction.